Strategi Perencanaan Pajak (Tax Planning) dalam Efisiensi Pajak Penghasilan Badan pada PT. EPM - Assifa Diartasya Paramitha; Artie Arditha; Arif Makhsun (Politeknik Negeri Lampung, 2021)
This writing aims to find out whether PT EPM has previously implemented tax planning of income owed to its company, know the income tax planning strategy that can be applied to PT EPM, and know the influence when implementing tax planning (tax planning) of PT EPM income. Primary data used in the form of interviews is to get company information that is not listed in the form of documents, then secondary data used in the form of income / loss statements and annual tax returns of PT EPM Agency in 2019. Data analysis methods use quantitative and qualitative methods based on numbers and things that happen within the company. Based on the results and discussions known PT EPM has never implemented income tax planning owed by the agency so that the author provides input on income tax planning strategies that can be applied by PT EPM which can then be known influence on the implementation of income tax planning strategy (tax planning) on PT EPM.